Transcutaneous auricular vagal nerve stimulation releases extrapineal melatonin and reduces thermal hypersensitivity in Zucker diabetic fatty rats - Wang, Shuxing; Li, Shaoyuan; Zhai, Xu; Rong, Peijing; He, Jietao; Liu, Lina; He, Xinxin; Liu, Wenguo (Frontiers in Neuroscience, 2022)
Type 2 diabetes (T2D) is the most common comorbidity of COVID-19, and both are related to the lack of circulating melatonin. In addition, chronic pain is a common sequela of both COVID-19 and T2D. Using a neuropathic pain model produced by sciatic nerve chronic constriction injury in Zucker diabetic fatty rats, a verified preclinical genetic T2D neuropathy animal model, this study aimed to show that transcutaneous auricular vagal nerve stimulation (taVNS) could elevate plasma melatonin concentration, upregulate the expression of melatonin receptors (MTRs) in the amygdala, and relieve peripheral neuropathic pain. Furthermore, taVNS would restore melatonin levels and relieve pain even in pinealectomized rats. On the contrary, intraperitoneally injected luzindole, a melatonin receptor antagonist, would attenuate the antinociceptive effects of taVNS. In conclusion, the mechanism of the therapeutic effect of taVNS on chronic pain involves the release of extrapineal melatonin and the positive regulation of the expression of central MTRs. This beneficial efficacy should be considered during COVID-19 rehabilitation in individuals with diabetes.